2012
DOI: 10.1007/s10875-012-9654-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Outcome Despite Full Lympho-Hematopoietic Reconstitution After Allogeneic Stem Cell Transplantation in Atypical Ataxia Telangiectasia

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) has not been a therapeutic option in ataxia telangiectasia (AT) due to overwhelming toxicity of conditioning in the context of the global DNA repair deficiency. Furthermore HSCT is unable to cure neurological involvement of AT. We report on a Turkish child with a Hyper IgM phenotype disorder, in which clinical aspects of AT were absent and thus, AT not diagnosed. He was transplanted with a reduced toxicity, but full intensity conditioning regimen compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…18,26 In the few published approaches, it becomes clear that the conditioning regime prior to the clinical application of bone marrow cells is the critical factor that determines patient outcome and that the balance between the toxicity and the ablative effect is essential. [12][13][14] Recently, we and others have demonstrated that BMT significantly improves the immunological phenotype, weight gain and fitness, and inhibits tumorigenesis in Atm-deficient mice. 10,11 However, BMT using a non-myeloablative host-conditioning regimen failed to reach a full donor chimerism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,26 In the few published approaches, it becomes clear that the conditioning regime prior to the clinical application of bone marrow cells is the critical factor that determines patient outcome and that the balance between the toxicity and the ablative effect is essential. [12][13][14] Recently, we and others have demonstrated that BMT significantly improves the immunological phenotype, weight gain and fitness, and inhibits tumorigenesis in Atm-deficient mice. 10,11 However, BMT using a non-myeloablative host-conditioning regimen failed to reach a full donor chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…10 Experience in the transplantation of A-T patients so far is limited and no transplantation strategy exists. [12][13][14] In other genomic instability syndromes, such as Fanconi anemia (FA), Nijmegen breakage syndrome (NBS) or DNA ligase IV deficiency, BMT has been successfully used. [15][16][17][18] In FA, continuous improvements to the approach to BMT over the last 20 years have resulted in reduced regimen-related toxicity, superior engraftment and less GVHD, leading to improved survival.…”
Section: Introductionmentioning
confidence: 99%
“…One patient was conditioned with 36 g/m 2 treosulfan and 150 mg/m 2 fludarabine and transplanted from an HLA-matched-related donor died after 8 months due to encephalopathy and hepatic toxicities, but the patient was transplanted for a misdiagnosed immunodeficiency, and the A-T diagnosis was made post-mortem. 7 The second patient was diagnosed with A-T and conditioned with 10 g/m 2 cytarabin and 150 mg/m 2 fludarabine before transplantation for acute leukaemia. The patient never went into remission and died 10 weeks after HSCT due to leukaemia progression (Persis Amrolia, personal communication, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Currently the only bone marrow transplantations that have been performed on A-T patients have been used to treat the presence of leukemias or other immunological abnormalities in these individuals (Ghosh, Schuster et al, 2012, Ussowicz, Musial et al, 2013. However, if a preventive approach, in which BMT were to occur before the occurrence of any hematopoietic malignancies, were beneficial enough to outweigh the risks associated with the transplantation procedure, such therapy may be worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies utilize HSCs (isolated or in combination with other cells) from bone marrow and umbilical cords for transplantation (Daley, 2012). (Ghosh, Schuster et al, 2012). BMT was successful in this patient with full lympho-hematopoietic reconstitution.…”
Section: Introductionmentioning
confidence: 95%